Correction to: Nitrogen acquisition, net production and allometry of Alnus fruticosa at a young moraine in Koryto Glacier Valley, Kamchatka, Russian Far East - Takahashi, Koichi; Homma, Kosuke; Doležal, Jiří; Yamagata, Kotaro; Vetrova, Valentina P; Hara, Toshihiko (Journal of plant research, 2018)
In the original publication of the article, one of the author names was published incorrectly as "Jiri Dorezal". The correct name is Jiří Doležal.